Male reproductive organs of Apis dorsata - Koeniger, Gudrun; Mardan, Makhdzir; Ruttner, Friedrich (Elsevier, 1990)
Based on an examination of a large number of everted copulatory organs of Apis dorsata drones, a new description of the structure is given (fig 1 c), which differs from previous publications. The result is of significance for classification within the genus Apis.